2011
DOI: 10.1152/ajpgi.00145.2011
|View full text |Cite
|
Sign up to set email alerts
|

Fast food diet mouse: novel small animal model of NASH with ballooning, progressive fibrosis, and high physiological fidelity to the human condition

Abstract: Although there are small animal platforms that recapitulate some of the histological features of nonalcoholic fatty liver disease, there are no small animal models of nonalcoholic steatohepatitis (NASH) with consistent hepatocellular ballooning and progressive fibrosis that also exhibit fidelity to the human condition physiologically. We examined the metabolic and histological effects of a diet on the basis of the composition of “fast food” (high saturated fats, cholesterol, and fructose). Mice ( n = 8 in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
354
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(393 citation statements)
references
References 64 publications
25
354
1
1
Order By: Relevance
“…Other models elicit steatosis, accompanied by manifest inflammation or severe cell damage. A novel dietary model caused characteristics similar to our model, including microvesicular steatosis but without evidence of severe inflammation after receiving a fast food diet, 34 though no data on resection or regeneration are available for this model yet. In our model, 6 weeks of WD feeding did not change cytokine release or induce severe inflammation and hepatic cell death before and after PHx.…”
Section: Discussionmentioning
confidence: 80%
“…Other models elicit steatosis, accompanied by manifest inflammation or severe cell damage. A novel dietary model caused characteristics similar to our model, including microvesicular steatosis but without evidence of severe inflammation after receiving a fast food diet, 34 though no data on resection or regeneration are available for this model yet. In our model, 6 weeks of WD feeding did not change cytokine release or induce severe inflammation and hepatic cell death before and after PHx.…”
Section: Discussionmentioning
confidence: 80%
“…Vehicle A prior in vivo study demonstrated the deleterious effects of increased dietary saturated fat by feeding mice a socalled "fast-food diet" that was high in saturated fat and cholesterol. These mice developed pathological symptoms of nonalcoholic steatohepatitis (NASH), in contrast to mice fed a typical high-fat diet that only developed simple steatosis without NASH symptoms ( 11 ). In vitro lipotoxicity experiments in a variety of cell lines, including Chinese hamster ovary (CHO) cells ( 10,12,13 ), pancreatic ␤ cells ( 14,15 ), breast cancer cells ( 16 ), and hepatic cells ( 6,9,(17)(18)(19), have shown that SFA overexposure is characterized by expression of proinfl ammatory cytokines, endoplasmic reticulum (ER) impairment, elevated reactive oxygen species (ROS), and eventual apoptosis without signifi cant TAG formation.…”
Section: Preparation Of Fa Solutionsmentioning
confidence: 94%
“…C56Bl/6J mice were purchased from Jackson Laboratory (Bar Harbor, ME). Twelve-week-old mice were fed either chow or a diet high in saturated fat, fructose, and cholesterol (FFC) for 24 weeks, as previously described ( 26 ). This diet recapitulates the pathologic features of human NASH.…”
Section: Mouse Studiesmentioning
confidence: 99%